[2,6-Bis(p-tolyliminomethyl)pyridine-kappa N-3,N `,N `']dichloridocopper(II) - Li, Xiao-Ping; Zhao, Jian-She; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, [CuCl2(C21H19N3)], lies on a twofold rotation axis that passes through the N-pyridyl-Cu bond; this symmetry element relates one half of the organic ligand to the other as well as one Cl ligand to the other. The three N atoms span the axial-equatorial-axial sites of the trigonal-bipyramidal coordination polyhedron; the geometry of the Cu-II atom is 31% distorted from trigonal-bipyramidal (towards square-pyramidal along the Berry pseudorotation pathway).